User Interface Designs Of An Educational Mobile Application: A Study Of Qiraat Teaching And Learning - Zulkifly Mohd Zaki; Khairul Anuar Mohamad; Syahidatul Fitriah Ishak (Hindawi, 2024)
Indexed by WOS/SCOPUS/ERA